Perancangan Sistem Inventory Berbasis Web Menggunakan Framework Flask : PT. Gagas Mitra Jaya (Area Salatiga) - Ma’arif, Oktaviano Miftahqul; Kurniasih, Tatit (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Research was conducted to build web-based inventory system at PT. Gagas Mitra Jaya in Salatiga as solution to the challenges in process of recording materials owned by technician. The research method used hybrid waterfall-agile. System design uses use case and activity diagrams in UML to describe flow of system creation, which involves the process of collecting data through interviews and questionnaires. The development uses Python, Flask, VS Code IDE, and PostgreSQL. This selection based on considerations of flexibility, accessibility, ease of integration, and faster update capabilities. The code architecture is MVC (Model-View-Controller), a development concept that divides data structures, system logic and interfaces on websites. The system designed called GNS (Gagas Network Supplies) has main menu that includes picking up, using and returning materials to record material usage, as well total item menu that summarizes material stock. The GNS system is expected to provide better service processes, more effective stock monitoring, higher inventory accuracy, and flexibility in business growth.